(untitled) (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
Ironic detective is a relatively new genre in literature. Its development dates back to the middle of the twentieth century and continues up to the present days. The final crystallization of the genre is taking place in our time. The works of Polish author Joanna Chmielewska became one of the first examples of ironic detective stories. However, the French literature of the twentieth century also has notable representatives of the genre. The present article examines the peculiarities of the irony functioning in the detective genre, in the context of the work of the popular modern French writer Daniel Pennac. We distinguish irony as a means of comic and as a principle of work organization, which is inherent in the genre of ironic detective. Consideration of the ironic detective is impossible without a brief analysis of the detective development stages as a whole, therefore, the article also deals with the genesis of the detective genre from the classic to the French novel-noir. The emphasis will rest on the peculiarities of the ironic detective’s development. Using D. Pennac’s novel The Scapegoat as an example (the French edition is called Au bonheur des ogres, originally published in 1985), the features of the genre, alongside their manifestations at the content and formal level are illustrated. The article focuses on the fact that naturalistic details, scenes of cruelty, evil and chaos, caused by the consequences of the Second World War, are weakened due to ironic characteristics, stereotypes, as well as the very attitudes of the author and the narrator towards the surrounding world. The research proves that the analysed genre is an artistic form of a panoramic view of the society of the 80s with its false ideals and its consumerism.